Do organizational justice and leadership trust improve village-owned enterprises performance? organizational learning as mediating - Basri, Yesi Mutia; Anatasya, Salsa Diva; Yasni, Hariadi; Taufik, Taufeni; Putra, Atiton Martwo; Lutviana, Ika; Dewi, Rafina; Indra Praja, Damara Putri Hestia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research aims to investigate the effects of organizational justice, trust in leadership, and organizational learning on the performance of Indonesian village-owned enterprises (VOEs).Design/Methodology/Approach: The data for this study were collected using a questionnaire survey to 855 respondents affiliated with VOEs in the regencies of Kuantan Singingi, Rokan Hulu, Meranti, and Indragiri Hilir. The data analysis was performed utilizing SmartPLS, a software tool often employed in academic research for structural equation modeling and path analysis.Research findings: The study's findings uncovered notable positive correlations between organizational justice and trust in leadership with the performance of VOEs. Furthermore, organizational learning served as a mediator in the correlation between organizational justice or trust in leadership and the performance of VOEs.Theoretical contribution/Originality: According to the principles of social exchange theory, individuals are more likely to exhibit increased levels of contribution and commitment towards their organization when they see fair treatment and possess a sense of trust in their leaders.Practitioner/Policy implication: This study highlights the significance of establishing a trustworthy atmosphere inside virtual organizational environments of VOEs to foster organizational learning and performance.Research limitation/Implication: By promoting fair practices, building trust in leadership, and encouraging continuous learning, VOEs can improve their organizational performance.